A base-stabilized germylenyl silaneditelluroate and 1,3-diaza-2-silaallylgermylene - Muhammad Luthfi Ismail (2021)
The trapping of a transient base-stabilized germylenylsilylene by elemental tellurium and arylazide is described. The reaction of the potassium 2-imino-5,6-methylenedioxylphenylgermylidenide [L GeK] (L = 2-imino-5,6-methylenedioxylphenyl) with the amidinato chlorosilylene [L SiCl] {L = PhC(NtBu) } in THF at –78 °C afforded the transient base-stabilized germylenylsilylene [L SiGeL ] (3). It was unstable in solution, but can be trapped by reacting with elemental tellurium and 2,6-diisopropylphenylazide ArN (Ar = 2,6-iPr C H ) to form the first base-stabilized germylenyl silaneditelluroate [L GeTeSi(=Te)L ] (4) and 1,3-diaza-2-silaallylgermylene complex [{L Si(NAr) }GeL ] (5), respectively. In these reactions, elemental tellurium and ArN insert into the :Si–Ge: bond in 3, followed by oxidation of the Si center with the substrates to form compounds 4 and 5, respectively. Compounds 4 and 5 were characterized by X-ray crystallography. iminophenyl iminophenyl amidinate amidinate 2 amidinate iminophenyl 3 2 6 3 iminophenyl amidinate amidinate 2 iminophenyl 3